Prestação de contas de convênios com recursos do FNDCT na FINEP: proposta de orientações aos convenentes - Azevedo, Carla Alessandra Rodrigues de Souza de (2014)
This research target is to provide accurate information for supplying the agreement manager with the necessary conditions to present accountability over a larger probability of approval by FINEP. The causes of the most frequent errors found in the financial implementation of projects that prevent the adoption of accountability in the analysis were investigated. The research has been done in two steps: documental research and data treatment. The first step was consisting of qualitative data collection and document analysis. Period studied was between January 1st, 2013 until November 30, 2013 - most recent ones, with agreements signed between 2001 and 2012. In this research were considered all analyzed agreements in that period referred, supported by FNDCT resources for studies and research development, analyzed by FINEP with at least one impropriety. Documental research has been realized at department DPCl in charge for the following - up of financial execution in FINEP agreements. Just to inform that 2476 agreements were analyzed throughout 2013; being 1248 approved and 1228 with some kind of impropriety. Second step has been quantitative, has been by saturation, using descriptive statistics with data exploratory analysis. Data treatment has been realized from the observed frequency distribution. As research result it can be observed that the ten most recurrent improprieties correspond to 90 % of all period. Before this fact there can be some proposal to orienting the agreements, through one FAQ at FINEP site, showing already signed agreements with FNDCT resources, easy understand and plain access.